Role of platelets during innate immunity to Streptococcus pneumoniae pneumonia - Dreimanis, Kristoffer (2008)
Thrombocytopenia is a common feature in severe infection and the extent of the thrombocytopenia has been correlated to the clinical prognosis. However the pathophysiology behind this phenomenon is not completely understood. Research in the last decade has shown that thrombocytes possess several antimicrobial properties, suggesting that they might play a still unknown role in innate immunity. Moreover platelets are known to sequestrate out into lung tissue in response to stimuli like lipopolysaccharide (LPS) and septicaemia. Streptococcus pneumoniae is a common cause of severe community aquired pneumonia and septicaemia. In this project I show that platelets in vitro are activated by S. pneumoniae and can release antimicrobial peptides in response to thrombin. This occurs independent of interactions with other cells. In vivo, I show that platelet deficiency results in increased bacterial numbers within the lungs in a mouse model of S. pneumoniae pneumonia. Histopathological examination of the lungs indicates that platelets co-localise with the bacteria –and may "trap" them within lung tissue. I conclude that platelets contribute to innate immunity to S. pneumoniae pneumonia identifying a potential therapeutic target for patients with severe infection.